Photodynamic Treatment of Titanium Dioxide Nanoparticles is a Convenient Method of Adenoviral Inactivation - Povnitsa, O.Y.; Zahorodnia, S.D.; Artiukh, L.O.; Zahornyi, M.M.; Ievtushenko, A.I.; Повниця, О.Ю.; Загородня, С.Д.; Артюх, Л.О.; Загорний, М.М.; Євтушенко, А.І. (PH "Akademperiodyka" of the NAS of Ukraine, 2023)
Today, the search for safe ways to inactivate pathogens is becoming especially relevant in connection with the coronavirus pandemic. Standard methods using chlorides and ultraviolet irradiation have disadvantages related to toxicity and low efficiency. Photodynamic inactivation involving nanoparticles is already used to disinfect water and air from microorganisms and enveloped viruses such as human herpes simplex virus, vesicular stomatitis virus, human immunodeficiency virus, and hepatitis B and C viruses. The aim of this work was to evaluate the possibility of the inactivation of human adenovirus type 5 in an organic medium using titanium dioxide irradiated with ultraviolet light. Methods. The nanosized titanium dioxide material was obtained by the thermal decomposition of a suspension of hydrated titanium dioxide TiO(OH)2 (metatitanic acid). The analysis of the morphology of the TiO2 nanopowder was carried out using electron scanning microscopy (SEM), which showed that TiO2 nanopowder contains soft aggregates of nanoparticles mostly 20‒30 nm in size. Cytotoxicity, virulicidal and antiviral action of titanium dioxide were determined by standard methods using (3-(4,5-dimathylthiazol-2-yl)-2,5-dipheniltetrazolium bromide (MTT). The titanium dioxide suspension was irradiated at a distance of 20 cm from 1 to 30 min with a bactericidal UV lamp (OBB15P, BactoSfera, Poland (254 nm)). The concentration of nanoparticles for irradiation was 1.0 mg/mL. Adenovirus suspension with titer 6.0 log10 TCID50 /mL was added to the nanoparticles immediately after irradiation. The titer of virus synthesized in the presence of titanium dioxide was determined by the end of the virus dilution, which causes 50% of the cytopathic effect of the virus on cells. All studies were performed in three replicates; the number of parallel determinations was three. Results. A dose-dependent effect of titanium dioxide nanoparticles on the viability of Hep-2 cells was revealed. At the NPs concentration of 1 mg/mL, quite a low cell viability was observed (32—39%), with a decrease in concentration to 0.1 and 0.01 mg/mL, the NPs were less toxic (cell viability was in the range of 62—90%). The TiO2 NPs dissolved in glycerin-water had no virulicidal effect, as the virus titer was similar to the control values. Instead, NPs dissolved in propanediol-ethanol reduced the infectious titer of the virus by 6.0 log10, which indicates their high virulicidal effect. The absence of an antiviral effect was shown when NPs were added to infected cells. A decrease in the virus titer by 4.5‒5.0 log10 was recorded uponitsinteracting with irradiated NPs for 1‒30 min. The effect persisted for 3 h after exposure to NPs. Conclusions. The cytotoxic, virulicidal, and antiviral effects of optically active TiO2 nanoparticles were determined in optimal conditions. Regardless of the solvent, NPs had low toxicity at a concentration of 0.1 mg/mL. The TiO2 NPs dissolved in glycerin-water had no virulicidal effect; but dissolved in propanediol-ethanol reduced the infectious titer of the virus by 6.0 log10, which indicates its high virulicidal effect. NPs in a propanediol-ethanol solution, irradiated with UV for 1‒30 min, completely inhibited adenovirus reproduction. NPs in a glycine-water solution reduced the virus titer by 0.5 log10. The control with NPs without irradiation slightly reduced the virus titer (by 0.45 log10). The ability of NPs to completely inactivate adenovirus was maintained for 3 h. It was shown for the first time that the non-enveloped HAdV5 virus could be efficiently inactivated by UV-induced TiO2 photocatalysis.